Kegiatan Public Relations B Radio 95.6 FM Dalam Menghadapi Tantangan Media Di Era Digital - Putri Aprilia (Jurnal Komunikasi dan Bisnis, 2019)
The existence of the internet as a result of the technology and communication development has forced the change from analog systems to digital. Entering the digital era like this is a challenge for conventional radio, one of them is PT. Radio Swara Burinyay (B Radio). Even though it is under the auspices of renowned radio management such as Ardan Group, the obstacle in developing a business in the digital era like this is not easy. From the number of listeners who have not yet reached the target, the number of advertisers is declining and the challenges with competitors, both other conventional and digital media, require the management of the company to make the right communication strategy to maintain B Radio's existence. With qualitative research methods and descriptive approaches the results of this study are through Public Relations activities in the Public Relations and Promotion division, B Radio takes responsibility in promotionl and branding activities for reach the company’s goals. This promotion activity is carried out through collaboration with clients to be able to optimize the branding activities carried out by B Radio, the strategy of promoting in conventional media and digital media is also done to increase brand awareness. Branding activities carried out by B radio can be through on-air, off-air and online broadcast programs. These activities make B Radio last for 15 years now. However, B Radio still has to optimize the use of social media so that it can always attract listeners with current things.